Learn Mac applications : Mac video training - Garay, Paul (Peachpit Press, 2010)
"Learn About Your Mac's Application Folder. Let MacVideoTraining.com make your transition as easy as possible with our expert video tutorials that show you the how-to's of using Mac OS X Snow Leopard. The Mac comes with a bunch of really cool and useful apps. We'll show you how to use Apple's most popular applications to effortlessly set up and configure your email, manage your contacts & calendars, and much more."--Resource description page.